Research on Precise Landing of Rotor UAV Based on Multi-Sensor Fusion - Li, Jintang (International Journal of Computer Science and Information Technology, 2024)
With the rapid development of drone technology, the autonomous landing of drones has become a current research hotspot. This article introduces an autonomous drone landing system based on multi-sensor fusion. The system combines GPS, IMU, visual sensors, LiDAR, and other sensor data through Kalman filtering to achieve data fusion and improve the positioning accuracy and stability of the drone during landing.